Trend 2004 - 2011. Statistics Canada. CANSIM: Children and Youth - Crime and Justice | Country: Canada | Province: Newfoundland and Labrador | Table: Youth custody and community services (YCCS), admissions and releases to correctional services | Variable: Youth admissions, Custody and supervision | Units: #, 2004-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-025. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Children and Youth - Crime and Justice | Country: Canada | Province: Newfoundland and Labrador | Table: Youth custody and community services (YCCS), admissions and releases to correctional services | Variable: Youth admissions, Custody and supervision | Units: #, 2004-2011. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-025. Dataset: Provides statistics on the incidence of youth crime in Canadian society; appearances, charges, and cases in youth courts; sentencing outcomes; youth in correctional services; and criminal victimization of youth. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Criminal Justice and Law Enforcement, Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Juvenile Correctional Facilities, Crime, Corrections, Juvenile Delinquency, Correctional Systems, Juvenile Offenders, Criminal Justice, Children, Adolescents